INTEGRATED TEACHING OF FOREIGN LANGUAGES AS A PEDAGOGICAL PROBLEM - Ірина Міркович (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article deals with the problem of integrated teaching of foreign languages. The main features of integrated teaching process are highlighted in this research. The difference between integrated teaching foreign languages and teaching on the basis of inter-subject connections has been revealed. The aims of these two kinds of teaching have been outlined. The essence of pedagogical integration has been disclosed. It has given a way to determine two kinds of integrity (subject and procedural one), and present their description in the article. It has been determined, that in the process of integration teaching methods of subject content, adequate to the methods of teaching foreign languages are used. As a result the subject knowledge and the foreign language knowledge are acquired in the integrated process of teaching.